Tipping of the double-diffusive regime in the southern Adriatic Pit in 2017 in connection with record high-salinity values - F. L. L. Amorim; J. Le Meur; A. Wirth; V. Cardin (Ocean Science, 2024)
In double-diffusive mixing, whenever salinity and temperature decrease with depth, the water column is either unstable or predisposed to a state called salt fingering (SF), which exhibits increased vertical mixing. Analysis of a high-frequency time series of thermohaline data measured at the EMSO-E2M3A regional facility in the southern Adriatic Pit (SAP) from 2014 to 2019 reveals that in the south Adriatic, SF is the dominant regime. The same time series shows the presence of a very saline core of the Levantine Intermediate Water that penetrated with unprecedented strength during the winter of 2016/17 at around 550 dbar and even higher-salinity water above. The effect of strong heat loss at the surface during that winter allowed deep convection to transport this high-salinity water from the intermediate to the deep layers within the pit. This resulted in an increased predisposition to SF throughout the water column. In the subsurface layer (350 to 550 dbar) the increase is from 27 % to 72 % of observations. We observe an alteration of vertical stratification throughout the water column during the winter of 2016/17 from a stratified water column to an almost homogeneous water column down to 700 dbar, with no return in the following years.